1995
DOI: 10.1177/0146167295211006
|View full text |Cite
|
Sign up to set email alerts
|

Folk Theories about Sex and Race Differences

Abstract: In a study assessing the nature of folk theories about the causes of sex and race differences and correlates of these theories, 464 undergraduates completed questionnaires concerning (a) causes of sex and race differences (e.g., socialization, opportunities, and biological factors), (b) the ease of eliminating differences, (c) perceptions of variability within and between the sexes, (d) intolerance of ambiguity, and (e) values concerning research on sex differences. Folk theories are similar for sex and race: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
0
10

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 37 publications
3
147
0
10
Order By: Relevance
“…More prejudiced persons may have a greater desire for clear distinctions between real social groups. Martin and Parker (1995) showed that students who were intolerant of ambiguity were more likely to believe that sex and race differences were due to biological factors rather than socialization factors. Blascovich, Wyer, Swart, and Kibler (1997) observed that racially prejudiced persons take longer to categorize racially ambiguous faces, and may also be more motivated to categorize them.…”
Section: Discussionmentioning
confidence: 99%
“…More prejudiced persons may have a greater desire for clear distinctions between real social groups. Martin and Parker (1995) showed that students who were intolerant of ambiguity were more likely to believe that sex and race differences were due to biological factors rather than socialization factors. Blascovich, Wyer, Swart, and Kibler (1997) observed that racially prejudiced persons take longer to categorize racially ambiguous faces, and may also be more motivated to categorize them.…”
Section: Discussionmentioning
confidence: 99%
“…In the years since these early articles, however, gender schema theorists and other cognitive researchers have elaborated how gender schemas develop and how their content may be learned (Liben & Bigler, in press). The development of gender schemas was extensively discussed in several review chapters (Martin, 1999;Martin & Halverson, 1987) and in the Handbook of Child Psychology (Ruble & Martin, 1998), as well as being the topic of a number of empirical studies (Bigler, Jones, & Lobliner, 1997;Fagot & Leinbach, 1989;Levy & Carter, 1989;Martin & Parker, 1995). Moreover, there is an extensive literature on the topic of schema development within social and developmental psychology.…”
Section: Discounting Cognition: Moving Against Integrationmentioning
confidence: 99%
“…While belief in the biological determination of sexual orientation is correlated with tolerance towards lesbians and gay men, beliefs in biological determination are also correlated with prejudice and stereotyping of other minority groups (c.f., Bastian & Haslam, 2006;Keller, 2005;Martin & Parker, 1995;Prentice & Miller, 2007;Morton, Postmes, Haslam, & Hornsey, 2009;Williams & Eberhardt, 2008;Yzerbyt, Rocher, & Schadron, 1997). This pattern of results has lead researchers to wonder if sexual prejudice is a 'special case' in this literature (e.g., D. Bem, 1998;Haslam et al, 2002;Jayaratne et al, 2006).…”
Section: Essentialist Thinking and Prejudicementioning
confidence: 99%